Relief of signs and symptoms in patients with tempromandibular disorders using occlusal stabilization splints equilibrated by T-scan versus articulating foil: a randomized clinical trial - Sarah Eman Abdelsalam; Ashraf Emil Eskandar; Ramy Maher Ghaly; Mohamed Amr Elkhashab (Brazilian Dental Science)
Objective: To evaluate the relief of signs and symptoms of temporomandibular disorders (TMDs) after splint equilibration via two methods: articulating foil and T-scan. Material and Methods: Twenty-eight patients with myofascial TMD were selected and divided into two groups. Each group were treated with additive CAD/CAM stabilization splints equilibrated using either articulating foil or T-scan. Pain reduction percentage, improvement in jaw function and pain free range of movements were assessed after 1 and 3 months. The data were analyzed by the repeated measures one-way ANOVA test followed by the Tukey’s post hoc test and the independent t- test. Results: There was a significant reduction in pain improvement in jaw function and pain free maximum opening within each group, without statistically significant differences (p>0.05) between both groups after 1 and 3 months. Conclusion: T-scan and articulating foil are both effective in stabilization splint equilibration.